2012
DOI: 10.1007/978-3-7091-0932-8_23
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Aspects of Mental Retardation in the Fragile X Syndrome: From Gene Mutation/s to Spine Dysmorphogenesis

Abstract: The Fragile X syndrome (FXS) is the most frequent form of inherited mental retardation and also considered a monogenic cause of Autism Spectrum Disorder. FXS symptoms include neurodevelopmental delay, anxiety, hyperactivity, and autistic-like behavior. The disease is due to mutations or loss of the Fragile X Mental Retardation Protein (FMRP), an RNA-binding protein abundant in the brain and gonads, the two organs mainly affected in FXS patients. FMRP has multiple functions in RNA metabolism, including mRNA dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 225 publications
(325 reference statements)
1
31
0
1
Order By: Relevance
“…19 Behavioral characteristics such as stereotypic movements and self-injurious behavior that are seen in 6/9 of the duplication subjects are also seen in fragile X syndrome and Smith-Magenis syndrome. 20,21 The likeable and happy disposition of 2q23.1 duplication subjects is also present in the Angelman syndrome phenotype. 22 The broad first toes, which are prevalent in the duplication subjects are also found in the RubinsteinTaybi phenotype; however, broad thumbs were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…19 Behavioral characteristics such as stereotypic movements and self-injurious behavior that are seen in 6/9 of the duplication subjects are also seen in fragile X syndrome and Smith-Magenis syndrome. 20,21 The likeable and happy disposition of 2q23.1 duplication subjects is also present in the Angelman syndrome phenotype. 22 The broad first toes, which are prevalent in the duplication subjects are also found in the RubinsteinTaybi phenotype; however, broad thumbs were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…FMRP forms large cytoplasmic ribonucleoparticles containing several other proteins (61) and RNAs (62,63). FMRP has been detected in P bodies and stress granules as well, where it forms translationally silent preinitiation complexes (64) (Figure 2).…”
Section: Figurementioning
confidence: 99%
“…High-throughput screenings supported by accompanying small scale studies have revealed that a wide array of neuronal mRNAs, with a large proportion encoding for presynaptic and postsynaptic proteins, is deregulated in the absence of FMRP, suggesting that concerted alteration of many proteins contributes to the FXS phenotype (62).…”
Section: Figurementioning
confidence: 99%
“…FMRP is an RNA-binding protein that can modulatethe localization, translation, and/orstabilityofcertain mRNAs. Absence of FMRP leads to fragile X syndrome, which is associated with defective synapse maturation (De Rubeis et al 2012).…”
Section: Regulation Of Translation Initiationmentioning
confidence: 99%